Infrastructure in the field of customs services: categorical and conceptual apparatus’ structural model and analysis - A. A. Lisitsa (Вестник университета)
The article analyzes scientific approaches to the definition of the terms “infrastructure”, “customs infrastructure”, “infrastructure in the field of customs services”, including in the context of functional aspects.   The study purpose is to form theoretical approaches and analyze the categorical and conceptual apparatus of the infrastructure in the field of customs as an institution of customs service, the consumers of whose services are the state, society and business.   The problem urgency is due to the ongoing changes in the external and internal environment of customs administration: the service orientation global vector of public administration.   The study objective is to form the author’s definition of the concept of service customs infrastructure, reflecting the target function, economic, functional, technical and social characteristics. The study concept is based on the theory of service-oriented customs administration in the field of customs services and on methodological approaches of the scientific school of the Russian Customs Academy. Based on the types’ analysis of customs services, the interests’ system of customs sphere subjects, a systematic approach to the concept under study has been substantiated, and a structural model of infrastructure in the field of customs services, classification of its elements according to vertical and horizontal principles have been developed. The analysis of regulatory and legal documents defining the standard requirements for the objects of production and information technology infrastructure of the automobile checkpoint is carried out. The results obtained allow us to propose the author’s definition of infrastructure in the field of customs services in a narrow and broad sense. Conclusions have beendrawn about the directions of improving the infrastructure in the field of customs services based on a service-oriented approach.